2020
DOI: 10.1007/s10862-020-09841-4
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Psychological Wellbeing Study: Understanding the Longitudinal Psychosocial Impact of the COVID-19 Pandemic in the UK; a Methodological Overview Paper

Abstract: The COVID-19 Psychological Wellbeing Study was designed and implemented as a rapid survey of the psychosocial impacts of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), known as COVID-19 in residents across the United Kingdom. This study utilised a longitudinal design to collect online survey based data. The aim of this paper was to describe (1) the rationale behind the study and the corresponding selection of constructs to be assessed; (2) the study design and methodology; (3) the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 51 publications
1
52
0
1
Order By: Relevance
“…The study conducted was based on cross-sectional data. The baseline data presented here is taken from the COVID-19 Psychological Wellbeing Study (Armour et al 2020) a longitudinal, online survey of the general adult (18+) population of the UK. The study was designed to assess and monitor the psychosocial impact of the COVID-19 pandemic on UK residents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted was based on cross-sectional data. The baseline data presented here is taken from the COVID-19 Psychological Wellbeing Study (Armour et al 2020) a longitudinal, online survey of the general adult (18+) population of the UK. The study was designed to assess and monitor the psychosocial impact of the COVID-19 pandemic on UK residents.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was administered as a rapid data collection exercise at the start of the UK's first COVID-19 lockdown, and it was administered both via a participant data collection panel (PROLIFIC) and via social media channels. After finalising data collection, the PI of the project compared the collected data to the UK census and reported that males were underrepresented compared to males in the UK population (Armour et al 2020). The resultant over-representation of females in the sample may have influenced the results as research has previously suggested that females have a higher morbidity rate than males regarding anxiety and depression (Matud 2017;Vlassoff 2007).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular groups such as males, older adults (65+), and lower levels of education were underrepresented. A detailed description of the sample characteristics and their comparison to UK-wide demographic can be found elsewhere (Armour et al, 2021). It is also important to acknowledge that the definition of key worker used in this study, although in line with the Government-defined categories, is broad.…”
Section: Limitationsmentioning
confidence: 99%
“…COVID-19 is a pandemic characterised by the need for change in the most fundamental aspects of human society, our interpersonal behaviors and social connections. Consequently, it is predicted to have major implications for mental health, and early evidence suggests some groups of people will be impacted disproportionately ( Armour et al., 2020 ; Fancourt et al., 2020 ; Kirby, 2020 ; O'Connor et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%